Resource recovery from acid mine drainage in membrane distillation crystallization - Chimanlal, Indira; Nthunya, Lebea N.; Quist-Jensen, Cejna; Richards, Heidi (Frontiers in Membrane Science and Technology, 2023)
Acid mine drainage (AMD) remains a global threat with no exception to South African water bodies and the environment. It promotes environmental challenges with emerging concerns on water security and drinking water pollution. This study evaluated membrane distillation crystallization (MDC) towards resource recovery from AMD. To ensure high process performance, polyvinylidene fluoride (PVDF) membranes evaluated in the current study were modified using hydrophobic nanoparticle additives and compared with PTFE-20 reference membranes. The produced permeate flux of PTFE-20 reference membranes and M4 (fSiO2NPs-modified membrane) were 2.426 kg·m-2·h-1 and 1.459 kg·m-2·h-1, respectively. Similarly, salt rejections were 99.96% and 97.52%, respectively. Based on single crystal x-ray diffraction and scanning electron microscopy analysis, MDC predominantly produced monoclinic gypsum (CaSO4·2H2O) with the C2/c space group. Also, crystal properties obtained in fSiO2NPs-modified and PTFE-20 reference membranes were comparable. Though a considerable amount of gypsum was obtained, membrane surfaces were characterized by traces of salt deposit, with possible membrane scaling leading to performance deterioration. The permeate conductivity increased rapidly at the highest water recovery factor, indicating membrane wetting caused by scaling.